Trial and error : the tale of a murderer who has to prove his own guilt - Berkeley, Anthony, 1893-1971 (Ambrose Chitterwick, 2001)
A terminally ill man decides to murder someone evil, but an innocent man is accused of the crime.The well-meaning killer tries to prove his guilt (aided by Ambrose Chitterwick), and hires a lawyer to prosecute himself.